Emotions in sustainability advancement : Multiactor experiences of the ongoing green transition - Haaja, Eini; Harikkala-Laihinen, Riikka (Elsevier, 2026)
Although individuals in various organizations are the agents of sustainability transitions, human experience remains an underdeveloped area in sustainability transition research. Building on interview data collected from public governance organizations, businesses, and their intermediaries, this qualitative study explores emotions experienced in the context of a European manufacturing industry undergoing a green transition. We find positive, negative, and mixed emotions targeted at various actors. Based on our findings, we formulate three propositions at different stages of the emotion elicitation process, reflecting actors’ interpretations and agency. By uncovering the sustainability transition-related emotions experienced by different actors, along with the objects of these emotions, this study sheds light on the system-wide complexity of advancing sustainability collectively. It also offers insights and recommendations for practitioners and paves the way for further research on emotions and their impact on sustainability transitions.